2021
DOI: 10.1111/jfbc.13728
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the fishy malodor from Bangia fusco‐purpurea via fermentation of Saccharomyces cerevisiae , Acetobacter pasteurianus , and Lactobacillus plantarum

Abstract: The present study aims to evaluate the deodorization of Bangia fusco‐purpurea using microorganism fermentation with commercial starter cultures of Saccharomyces cerevisiae, Acetobacter pasteurianus, and Lactobacillus plantarum. The results showed the fermentation with S. cerevisiae, A. pasteurianus, and L. plantarum resulted in significantly decreases (p < .05) of the fishy malodor in B. fusco‐purpurea. Among the three strains, S. cerevisiae was the best for reducing the fishy malodor. The optimal inoculum siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 40 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Some consumers of seaweed may be apprehensive about a "fishy" or "seafood" taste. Although many sensory tests don't report this issue, Du et al (2021) found that the removal of the compounds that cause this flavour have been successful [68]. In a study by Losada-Lopez et al ( 2021) examining consumer's perception of seaweed, the consumer's willingness to consume seaweed was negatively affected by neophobia [69].…”
Section: Sensory Properties and Consumer Perceptionmentioning
confidence: 99%
“…Some consumers of seaweed may be apprehensive about a "fishy" or "seafood" taste. Although many sensory tests don't report this issue, Du et al (2021) found that the removal of the compounds that cause this flavour have been successful [68]. In a study by Losada-Lopez et al ( 2021) examining consumer's perception of seaweed, the consumer's willingness to consume seaweed was negatively affected by neophobia [69].…”
Section: Sensory Properties and Consumer Perceptionmentioning
confidence: 99%
“…Inspired by a similar use of fermentation performed on Paratapes undulatus hydrolisates, Du et al, (2021) employed this process to reduce the concentrations of undesired volatile compounds present in Bangia fuscopurpurea. Fermentations with S. cerevisae, having achieved the highest reduction in undesired aromas, were further profiled via SPME-GC-MS.…”
Section: Seaweed Fermentation For Biosynthesis Of Other Valuable Comp...mentioning
confidence: 99%
“…In comparison, fermentation with Saccharomyces cerevisiae not only reduces fishy odors but also enhances fruit and floral aromas [17]. Therefore, researchers prefer to use S. cerevisiae to enhance the flavor of plant, seaweed, and fish products [20,21], which could be a practical method to enhance the flavor quality of food products made from S. japonica.…”
Section: Introductionmentioning
confidence: 99%